Efficacy and safety of teneligliptin in patients with type 2 diabetes mellitus: a Bayesian network meta-analysis - Zhu, Miao; Guan, Ruifang; Ma, Guo (Frontiers in Endocrinology, 2023)
Background: As a popular antidiabetic drug, teneligliptin has been used for over ten years, but its efficacy and safety has rarely been systematically evaluated. Methods: We systematically searched PubMed, Web of Science, Embase, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov. Data analysis was performed using R 4.2.3 and Stata 17.0 software. Each outcome was presented as a mean difference (MD) or an odds ratio (OR) along with 95% confidence interval (CI) and the surface under the cumulative ranking curve value (SUCRA). Results: 18 RCTs with 3290 participants with T2DM were included into this study. Generally, compared to placebo, sitagliptin, vildagliptin, metformin and bromocriptine, 20 mg of teneligliptin showed better efficacy in reducing HbA1c (MD [95% CI], -0.78 [-0.86 to -0.70], -0.08 [-0.36 to 0.19], -0.04 [-0.72 to 0.60], -0.12 [-0.65 to 0.42] and -0.50 [-0.74 to -0.26], respectively), fasting plasma glucose (FPG) (MD [95% CI], -18.02 [-20.64 to -15.13], 1.17 [-9.39 to 11.70], -8.06 [-30.95 to 14.35], -2.75 [-18.89 to 13.01] and -34.23 [-45.93 to -22.96], respectively), and 40 mg of teneligliptin also showed better efficacy in reducing HbA1c (MD [95% CI], -0.84 [-1.03 to -0.65], -0.15 [-0.49 to 0.19], -0.10 [-0.81 to 0.57], -0.18 [-0.76 to 0.39] and -0.56 [-0.88 to -0.26] , respectively), FPG (MD 95% [CI], -20.40 [-26.07 to -14.57], -1.20 [-13.21 to 10.38], -10.43 [-34.16 to 12.65], -5.13 [-22.21 to 11.66] and -36.61 [-49.33 to -24.01], respectively). Compared to placebo, 20 mg of teneligliptin showed no significant difference in incidences of hypoglycemia and gastrointestinal adverse events (OR [95% CI], 1.30 [0.70 to 2.19] and 1.48 [0.78 to 2.98], respectively), and 40 mg of teneligliptin showed no significant difference in incidence of hypoglycemia (OR [95% CI], 2.63 [0.46 to 8.10]). Generally, antidiabetic effect and hypoglycemia risk of teneligliptin gradually increased as its dose increased from 5 mg to 40 mg. Conclusion: Compared to sitagliptin, vildagliptin, metformin, bromocriptine and placebo, teneligliptin displayed favorable efficacy and acceptable safety in treating T2DM. 20 mg or 40 mg per day was the optimal dosage regimen of teneligliptin.